Successful treatment of actinic granuloma with intralesional steroid injection - Šujica, Ana (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2024)
Actinic granuloma (AG) is a rare dermatological condition with only a few dozen cases reported worldwide. Initially classified as a variant of granuloma annulare, it is now recognized as a distinct entity characterized by asymptomatic annular plaques in sun-exposed areas of the skin. The exact pathogenesis remains unclear, but it is believed to be an inflammatory response to sun damage, possibly involving injured elastic fibers. Numerous local and systemic therapeutic options exist, but no specific treatment guidelines have been established. We present a case of AG treated with intralesional application of triamcinolone acetonide in a 64-yearold male patient. We also discuss the most important clinical and histological characteristics and various treatment options.
Keywords: aktinični granulom; dermatologija; intralezijska terapija; možnosti zdravljenja; prikaz primera